Building Competitive Advantage and Business Success through Self-Efficacy, Product Diversity, and Promotion Strategy - Amelia, Emi; Okte, Muhamad Rizki Maulani; Hasanah, Ade Sobariah; Pratiwi, Vina Andita (Entrepreneurship Faculty, Universitas Garut, 2025)
Business success is essentially the success of a business in achieving its goals from all activities in a company, namely to achieve business success. The focus of this research is to explain the impact of self-efficacy, product diversity, competitive advantage, and promotion on business success in the creative industry. This research was conducted in Majalengka Regency, West Java, Indonesia. The respondents were creative economy industry players using purposive sampling technique. The data collection technique in this study used an online questionnaire via google form. The data analysis technique uses verification analysis, hypothesis testing and the coefficient of determination and is processed using SPSS. The conclusion of this study is that self-efficacy has a positive and significant effect on business success, product diversity has a positive and significant effect on business success, competitive advantage has a positive and significant effect on business success, promotion has a positive and significant effect on business success, and self-efficacy, product diversity, competitive advantage, and promotion have a positive and significant effect on business success.